2009
DOI: 10.1159/000235158
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a HeLa <i>Mx2</i>/Luc Reporter Cell Line for the Quantification of Human Type I Interferons

Abstract: Although antiviral assays have been the most widely available biological assays for interferons (IFNs), they are less sensitive and provide considerable interassay variation. In this study, we demonstrate a new reporter cell line, which is based on HeLa cells transfected with a plasmid containing a human Mx2 promoter driving a luciferase (Luc) cDNA. To characterize the specific gene expression profiles induced by interferon alpha, we analyzed the microarray results of interferon response gene expression induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…We therefore measured mRNA expression of the type I IFN-regulated genes IFIT1 and MX2 (42, 43) in B220 + splenocytes and kidney from additional cohorts of Irf5 +/+ RII. Yaa, Irf5 −/− RII.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore measured mRNA expression of the type I IFN-regulated genes IFIT1 and MX2 (42, 43) in B220 + splenocytes and kidney from additional cohorts of Irf5 +/+ RII. Yaa, Irf5 −/− RII.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite almost 60 years of active research in this field, the direct measurement of type I IFN protein in biological samples has remained elusive. Type I IFN mRNA is usually present at only trace levels in PBMCs from healthy individuals, and current ELISAs have proven either insensitive or unreliable, leading to the development of proxy assays based on type I IFN signaling (Hua et al, 2006; Niewold et al, 2009; Seo et al, 2009; Li et al, 2010; Berger Rentsch and Zimmer, 2011). Such presumed low levels of circulating IFN protein likely reflect the high biological potency of these cytokines, with most cell types expressing a type I IFN receptor.…”
Section: Introductionmentioning
confidence: 99%
“…These RGAs employed a variety of IFN responsive promoters including Mx, ISRE, GFAP [1626]. Using Mx2/Luc reporter cell line, Seo et al [23] reported the RGA is even more sensitive than the ISRE/Luc reporter cell line. While previous studies have provided strong evidences that RGA is advantageous compared to the traditional AVA with respect to simplicity, rapidity and reproducibility, optimization and/or modification of the RGAs also appear to be necessary since some systems are associated with narrow detection range or require extra steps after the addition of IFN.…”
Section: Discussionmentioning
confidence: 99%